Anthropological Dimension of Constructivism in the Culture of Presence - Dolska, Olga; Gorodiskaya, Olga; Tararoyev, Jakov (Studia Warmińskie, 2019)
To the authors’ mind human activity is more frequently based on Constructivism in spheres as science, epistemology, education, upbringing, number of living practices, etc. The authors emphasize if such approach relies on Enlightenment rationality there are many risks and negative consequences of it using what was obviously already in 20th century. The reason is in specific comprehension of subject that influences on imperfect anthropological dimension of the rationality. Analysing of its modification has necessarily led the authors to take into account the Culture of Presence idea in the process of anthropological dimension realisation. The Culture of Presence “clears” the place for a new “intellectual surrounding” where there is a need to leave the awful Constructivism position formed through metaphysical comprehension of subject. In the article there were proposed the categories of those culture, there emphasizes their relevance in new life conditions and there was analysed the Presence phenomenon in the contemporary scientists researches. The authors underline the Culture of Presence basis and implementations of this culture contribute to disappearance of self-contained subject. In the event situation the subject could be replaced by subjectivity capable to respond, to empathize, to be responsible for others, etc. The contemporary humanities need to renew anthropological dimension inasmuch as comprehension of it cannot be guided at traditional norms of Enlightenment rationality and metaphysics discourse.